The cup and the crown - Stanley, Diane (HarperCollins, 2012)
"At King Alaric's urging, Molly sets off on a quest for a magical loving cup (a goblet that binds people together), and her journey leads her to the hidden city of her ancestors, which proves to be as dangerous as it is mysterious"--